(untitled) (CIPEEX, 2022)
WASTE RECYCLING CONSISTS OF REUSING THE WASTE PRODUCED BY SOCIETY. IN BRAZIL IT IS STILL NOT VERY EXPLOITATIVE, AND MOST OF THEM GO, WHERE THEY WILL MAKE IT HAPPEN FROM LAND IN LANDFILL, WATER AND MOST OF IT. TO HELP IN THE SUSTAINABLE RESOLUTION OF THIS PROBLEM, THIS RESEARCH PROPOSES THE DEVELOPMENT OF AN SOFTWARE THAT MOST BENEFITS FROM RECYCLING AND HOW TO DISPOSE OF THIS WASTE. THE BIGGEST DIFFERENTIAL OF THE APPLICATION IS THE POSSIBILITY FOR THE INDIVIDUAL TO COME INTO DIRECT CONTACT WITH PEOPLE WHO WORK WITH THE COLLECTION OF RECYCLABLE WASTE. TO TRY TO USE THE VIABILITY OF PEOPLE, A SURVEY WAS CARRIED OUT USING A FORM OF QUESTIONS THAT ALREADY DO RECYCLING, THE AMOUNT OF PEOPLE WHO DO NOT RECYCLE AND THE VERIFICATION OF PEOPLE WHO DID OR AN SOFTWARE NEVER IN THEIR DAY TO DAY.